Kedudukan Bank Syariah dalam Penyelesaian Sengketa Melalui Arbitrase (Studi Perbandingan Indonesia dan Malaysia) - Muhammad Adil Maulana; Abdullah Kelib (Notarius, 2023)
AbstractThe development of Islamic banking into the global financial industry led to the development of Islamic banking products. It is possible there will be disputes relating to Islamic banking products. and requires a legal framework for dispute resolution truly "Islamic". This article discussed regarding the settlement of disputes through arbitration of Islamic banking in Indonesia and Malaysia, so hopefully will get an understanding of Islamic banking dispute resolution and arbitration role in developing an Islamic economics. The method in this article is a juridical-normative approach, that tried to synchronize the legal provisions applicable to the implementation of the case to be studied. Specifications of research were classified in descriptive analysis research. The result of this article is dispute settlement process through Badan Arbitrase National Indonesia and the Kuala Lumpur Regional for Arbitration beginning with the submission of arbitration agreement. After the examination process is completed then the award is decided by the arbitration is final and binding. National Sharia Arbitration and Kuala Lumpur Regional Arbitration for having similarities and differences. Settlement of Islamic banking disputes through arbitration Sharia should be returned to the application of the principles of Islamic Sharia are fully in favour of the economic advancement of Islam. Keywords: role; arbitration; Islamic banking disputes.AbstrakBerkembangnya perbankan Islam menjadi industri keuangan dan finansial global menyebabkan berkembangnya bentuk-bentuk produk bank Islam, sehingga, tidak tertutup kemungkinan akan terjadi sengketa berkaitan dengan produk-produk bank Islam. Perbankan Islam memerlukan kerangka hukum penyelesaian sengketa yang efisien, dan benar-benar “Islam”. Artikel ini membahas mengenai penyelesaian sengketa perbankan Islam melalui arbitrase di Indonesia dan Malaysia, sehingga diharapkan akan mendapat pemahaman mengenai penyelesaian sengketa perbankan Islam dan peranan arbitrase dalam mengembangkan ekonomi Islam. Metode pendekatan yang digunakan dalam artikel ini adalah pendekatan yuridis normatif, yaitu suatu pendekatan yang berusaha mensinkronisasikan ketentuan-ketentuan hukum yang berlaku dengan implementasinya terhadap kasus yang akan diteliti. Spesifikasi penelitian yang digunakan dalam penelitian ini digolongkan dalam penelitian deskriptif analisis. Hasil artikel ini adalah proses penyelesaian sengketa melalui Badan Arbitrase Syariah Nasional dan Kuala Lumpur Regional for Arbitration dimulai dengan adanya penundukkan melalui perjanjian arbitrase. Setelah proses pemeriksaan selesai, maka putusan yang diputus oleh kedua arbitrase ini bersifat final and binding. Badan Arbitrase Syariah Nasional dan Kuala Lumpur Regional for Arbitration memiliki kesamaan dan perbedaan. Penyelesaian sengketa perbankan Islam melalui arbitrase syariah harus dikembalikan kepada penerapan prinsip-prinsip syariah Islam yang sepenuhnya demi mengembangkan kemajuan ekonomi Islam.Kata kunci: peranan; arbitrase; sengketa perbankan Islam.